Early versus delayed (traditional) oral fluids and food for reducing complications after major abdominal gynaecologic surgery - Charoenkwan K. (2014)
Background: Traditionally postoperative oral intake is withheld until the return of bowel function. There has been concern that early oral intake would result in vomiting and severe paralytic ileus with subsequent aspiration pneumonia, wound dehiscence, and anastomotic leakage. However, supporting scientific evidence for this traditional practice is lacking and there are potential benefits from early postoperative oral intake. Objectives: To assess the effects of early versus delayed (traditional) initiation of oral intake of food and fluids after major abdominal gynaecologic surgery. Search strategy: We searched the Menstrual Disorders & Subfertility Group's Specialised Register of controlled trials, the electronic databases (MEDLINE, EMBASE, CINAHL), the Cochrane Controlled Trials Register, and the citation lists of relevant publications in April 2007. Selection criteria: Randomised controlled trials that compared the effect of early versus delayed initiation of oral intake of food and fluids after major abdominal gynaecologic surgery were considered. Early feeding was defined as having oral intake of fluids or food within the first 24 hours after surgery regardless of the presence or absence of the signs that indicate the return of bowel function and delayed feeding was defined after first 24 hours following surgery and only after clinical signs of resolution of postoperative ileus. Data collection and analysis: Studies considered were assessed for methodological quality criteria for inclusion. For dichotomous data, relative risks and 95% confidence intervals were calculated. Continuous data were examined using weighted mean difference and 95% confidence interval. Heterogeneity between the results of different studies were examined by using the forest plot of a meta-analysis, the statistical tests of homogeneity of 2 x 2 tables and the I2 value. Main results: Early commencement of oral fluids and food was associated with: increased nausea (one study, 195 patients; relative risk 1.79, 95% confidence interval 1.19 to 2.71), shorter time to the presence of bowel sound (one study, 195 patients; weighted mean difference - 0.5 day, 95% confidence interval -0.84 to -0.16), shorter time to first solid diet (two studies, 301 patients; weighted mean difference - 1.47 day, 95% confidence interval -2.26 to -0.68), and a trend toward shorter hospital stay (two studies, 301 patients; weighted mean difference -0.73 day, 95% confidence interval -1.52 to 0.07). The shorter hospital stay with early feeding was also evident in the study that reported length of hospital stay in median (-2 days, 4.0 days in early feeding group and 6.0 days in traditional feeding group). There was no significant difference in postoperative ileus, vomiting, and abdominal distension, time to presence of flatus, time to the first passage of stool, postoperative nasogastric tube placement, febrile morbidity, wound complications, and pneumonia. Authors' conclusions: Early feeding after major abdominal gynaecologic surgery is safe however associated with the increased risk of nausea and a reduced length of hospital stay. Whether to adopt the early feeding approach should be individualised. Further studies should focus on the cost-effectiveness, patient's satisfaction, and other physiological changes. Copyright © 2008 The Cochrane Collaboration. Published by John Wiley & Sons, Ltd.